2019
DOI: 10.1177/1071100719866472
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intermediate-term Outcomes of Total Ankle Arthroplasty in Primary and Ligamentous Post-traumatic Osteoarthritis

Abstract: Background: Ankle ligamentous injuries without fracture can result in end-stage ligamentous post-traumatic osteoarthritis, which may cause ligamentous imbalance after total ankle arthroplasty (TAA). However, outcomes of TAA in these patients are not well known. The purpose of this study was to evaluate intermediate-term clinical and radiographic outcomes of TAA in patients with ligamentous post-traumatic osteoarthritis and compare them with results of TAA for patients with primary osteoarthritis. Methods: We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Similar studies are limited by mixed PTOA cohorts. 9 Similar to our study, Lee et al 15 found no difference in outcomes and 5-year implant survivorship (91.3% vs. 95.8%) in POA and instability PTOA, respectively. Nieuwe Weme et al 10 as well demonstrated no difference in outcomes or 6-year implant survivorship between fracture and instability PTOA (87% vs. 79%, respectively).…”
Section: Discussionsupporting
confidence: 89%
“…Similar studies are limited by mixed PTOA cohorts. 9 Similar to our study, Lee et al 15 found no difference in outcomes and 5-year implant survivorship (91.3% vs. 95.8%) in POA and instability PTOA, respectively. Nieuwe Weme et al 10 as well demonstrated no difference in outcomes or 6-year implant survivorship between fracture and instability PTOA (87% vs. 79%, respectively).…”
Section: Discussionsupporting
confidence: 89%
“…However, in a more comprehensive analysis, Gaugler et al found no association between age and revision risk or clinical outcomes following TAR 53 . As many authors have suggested, TAR should remain a treatment option for younger patients, provided that a higher physical demand on the implant as a potential risk factor is considered by the practitioner and the patient 22,[54][55][56] .…”
Section: Discussionmentioning
confidence: 99%
“…Total ankle arthroplasty (TAA) has been steadily developed while overcoming the drawbacks of the past and is widely performed as a primary treatment for end-stage ankle arthritis [ 1 – 9 ]. Wound closure is an important final step for good cosmesis and minimizing surgical site infection [ 10 ].…”
Section: Introductionmentioning
confidence: 99%